2019
DOI: 10.4103/jrms.jrms_783_18
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness, neurocognitive, and body composition effects of fasting during Ramadan

Abstract: Background: We aimed to study the anatomical, physiological, and cognitive function of healthy individuals practicing fasting during the month of Ramadan. Measurements were taken 1 week before and 2 weeks after Ramadan fasting. Materials and Methods: Twelve healthy male individuals (mean age ± standard error of the mean: 34.3 ± 2.9 years; body mass index: 26.26 ± 1.4 kg/m 2 ) were assessed for various parameters before and after Ramadan fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, the cognitive tests were performed two days after fasting [ 74 ]. Iqbal et al tested cognition after two weeks of Ramadan fasting (one month) in males and found similar cognitive outcomes but significant improvements in spatial working memory [ 75 ]. For females, fasting for one month did not impact cognition even after two weeks of fasting [ 76 ].…”
Section: Intermittent Fasting (If): Ketogenic and Cognitive Potentialsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the cognitive tests were performed two days after fasting [ 74 ]. Iqbal et al tested cognition after two weeks of Ramadan fasting (one month) in males and found similar cognitive outcomes but significant improvements in spatial working memory [ 75 ]. For females, fasting for one month did not impact cognition even after two weeks of fasting [ 76 ].…”
Section: Intermittent Fasting (If): Ketogenic and Cognitive Potentialsmentioning
confidence: 99%
“…In contrast, ketone bodies are under-reported in fasting studies, and it is hard to predict their role on cognition during fasting. IF ketosis requires long-term metabolic adaptations to appear [ 72 ]; most of the fasting studies performed on healthy and young individuals have not exceeded one month of fasting, and they mostly resemble Ramadan fasting [ 73 , 74 , 75 , 76 , 79 ]. Others tested fasting in a single-day setting [ 73 , 78 , 81 ], which could have been met with psychological difficulties that require adaptation and impact the study outcomes [ 83 ].…”
Section: Intermittent Fasting (If): Ketogenic and Cognitive Potentialsmentioning
confidence: 99%
See 1 more Smart Citation